Flowering and seed production studies with special reference to natural self-pollination in a Pinus taeda L. seed orchard in the Eastern Transvaal - Hagedorn, S. F.(Siegfried Ferdinand) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1980.